Investigating the Effects of Cement Type and W/C Ratio on the Concrete Corrosion Using the Electrical Resistance Assessment Method - Moein Biglari; Amirhosein Sheykh Azami; Ali Kahidan; Ehsan Ghafari; Mohammad Ali Ghasemi (Salehan Institute of Higher Education, 2018)
Today, concrete is known as the most widespread material in civil projects. Up to now, many research works have been conducted concerning determination of concrete durability using various methods including the measurement of electrical resistance in concrete. The present article is an attempt for application of a new method for measurement of electrical resistance of non-conductive materials which is well suited for concrete. To determine the effects of cement type and water to cement ratio on the corrosion phenomenon the electrical resistance method was used. For this purpose use was made of 7 different water to cement ratios and two types of cement (type 2 and type 5). Drawing the electrical resistance diagrams, it was shown that with increase in the water to cement ratio, corrosion rate increases in concrete. Also application of type 5 cement results in a higher strength resistance with respect to cement type 2. On the other hand by increase in the age of concrete specimens, they showed greater resistance to the corrosion attacks.